If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + 6) + 2(x + 6) = 7x + -7 Reorder the terms: 9(6 + x) + 2(x + 6) = 7x + -7 (6 * 9 + x * 9) + 2(x + 6) = 7x + -7 (54 + 9x) + 2(x + 6) = 7x + -7 Reorder the terms: 54 + 9x + 2(6 + x) = 7x + -7 54 + 9x + (6 * 2 + x * 2) = 7x + -7 54 + 9x + (12 + 2x) = 7x + -7 Reorder the terms: 54 + 12 + 9x + 2x = 7x + -7 Combine like terms: 54 + 12 = 66 66 + 9x + 2x = 7x + -7 Combine like terms: 9x + 2x = 11x 66 + 11x = 7x + -7 Reorder the terms: 66 + 11x = -7 + 7x Solving 66 + 11x = -7 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 66 + 11x + -7x = -7 + 7x + -7x Combine like terms: 11x + -7x = 4x 66 + 4x = -7 + 7x + -7x Combine like terms: 7x + -7x = 0 66 + 4x = -7 + 0 66 + 4x = -7 Add '-66' to each side of the equation. 66 + -66 + 4x = -7 + -66 Combine like terms: 66 + -66 = 0 0 + 4x = -7 + -66 4x = -7 + -66 Combine like terms: -7 + -66 = -73 4x = -73 Divide each side by '4'. x = -18.25 Simplifying x = -18.25
| 9x-12y=8 | | 6(2c+10)=5(c+5) | | 4n^2-7=-7n | | 30/20=x/4 | | 5c+9=4z-1 | | 3+4(x-5)=34 | | 9(x+1)+4(x+1)=6x-6 | | -6+11=-5-2 | | x^7-6x^5+2x^4-5=0 | | 2p-3=11 | | 3+7n=1+6n | | ln^3x=5 | | 5k^2=6-k | | (x+1)+(y-2)=7 | | 4x+25=8x+37 | | 16-2w=5w+9 | | 8x=215-13x | | 65+7x+5x-5=180 | | 5x^3+2x^2-x=0 | | 4y=12x-5 | | 7p+14=p-4 | | 6n^2-8=-93 | | -132=-7d-4d | | 8+3e^3x=26 | | 25a^2+8=108 | | 3h+12h=18 | | -5+3m=2m+2 | | X/7=10/2 | | 70+x+80+x+40=180 | | 8+3e=26 | | n^2=6+n | | 0=-4u^2-31u-50 |